Pemahaman Orang Muda Katolik Di Paroki Santo Fransiskus Xaverius Pineleng Tentang Buah Dari Sakramen Tobat - Karolus Juan Tupan (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2026)
The Sacrament of Penance is one of the primary means of God's grace in the Catholic Church, which aims to forgive sins and restore human relationships with God and the Church. However, in pastoral practice, young people's understanding of this sacrament is often limited. This study aims to explore the understanding of Catholic Youth in the Parish of St. Francis Xavier Pineleng regarding the fruits of the Sacrament of Penance. The method used is a qualitative approach through in-depth interviews. The results of the study indicate that OMK St. Fransiskus Xavier Pineleng understand the fruits of the Sacrament of Penance as a means of forgiveness of sins, a source of inner peace, restoration of relationships with God and others, and spiritual strength to resist temptation. This study confirms that the Sacrament of Penance remains re